In situ surface engineering enables high interface stability and rapid reaction kinetics for Ni-rich cathodes - Wenshuai Guo; Wu Wei; Huawei Zhu; Yanjie Hu; Hao Jiang; Chunzhong Li (eScience, 2023)
Layered oxide cathodes with high Ni content promise high energy density and competitive cost for Li-ion batteries (LIBs). However, Ni-rich cathodes suffer from irreversible interface reconstruction and undesirable cracking with severe performance degradation upon long-term operation, especially at elevated temperatures. Herein, we demonstrate in situ surface engineering of Ni-rich cathodes to construct a dual ion/electron-conductive NiTiO3 coating layer and Ti gradient doping (NC90–Ti@NTO) in parallel. The dual-modification synergy helps to build a thin, robust cathode–electrolyte interface with rapid Li-ion transport and enhanced reaction kinetics, and effectively prevents unfavorable crystalline phase transformation during long-term cycling under harsh environments. The optimized NC90–Ti@NTO delivers a high reversible capacity of 221.0 mAh g−1 at 0.1C and 158.9 mAh g−1 at 10C. Impressively, it exhibits a capacity retention of 88.4% at 25 ​°C after 500 cycles and 90.7% at 55 ​°C after 300 cycles in a pouch-type full battery. This finding provides viable clues for stabilizing the lattice and interfacial chemistry of Ni-rich cathodes to achieve durable LIBs with high energy density.